Sound absorption characteristic of lightweight brick containing Expanded Polystyrene Beads (EPS) and Palm Oil Fuel Ash (POFA) - Kamarulzaman, Nurul Amirah (2020)
The main objectives of this research is to identify the sound absorption characteristic of lightweight bricks containing expanded polystyrene beads (EPS) and palm oil fuel ash (POFA). In order to fulfill the standard of a lightweight brick to be used as a building element, the physical and mechanical properties were test first. EPS was used as a sand replacement whereas POFA was used as a cement replacement. The bricks were casted with 0% to 50% of EPS and 0% to 25% of POFA and air cured for 7, 28 and 56 days. The bricks incorporated with 30%, 40% and 50% of EPS were considered lightweight bricks as they have a density below 1680 kg/m3 . The lowest density recorded for the brick sample with the maximum EPS and POFA content was 1320.52 kg/m3 after a curing period of 56 days. Bricks incorporated with varying percentages of EPS and POFA have strength values between 3.7 MPa to 21.3 MPa which are acceptable for load bearing and non-load bearing structures. The water absorption values recorded for these bricks were between 4.37% to 13.4%. The brick sample with 0% POFA and 50% EPS recorded the lowest water absorption values while the brick sample with 25% POFA and 0% EPS recorded the highest water absorption values. For the sound absorption test, at high frequency, the brick specimen with 25% POFA and 50% EPS recorded the lowest coefficient of 0.009 while the best sound absorption coefficient recorded was 0.467 for the brick sample with 0% EPS and 10% POFA. At low frequency, the bricks recorded a sound absorption coefficient of 0.89 to 0.998. Most The brick have excellent absorption at low frequency and good absorption at high frequency. Lastly, the density properties and sound absorption coefficient were found to be the most correlated due to the highest R 2 value of 0.9259 compared to other properties.